Quantitative proteomic analysis and replacement therapy identifies haptoglobin as a therapeutic target in a murine model of SLE-associated diffuse alveolar hemorrhage - Yan, Ninghui; Shao, Chenyi; Zhen, Yan; Zhang, Xueliang; Xia, Nana; Guo, Qiang (Frontiers in Veterinary Science, 2024)
Background: Diffuse alveolar hemorrhage (DAH) is a catastrophic clinical syndrome and one of the manifestations of pulmonary involvement in systemic lupus erythematosus (SLE), characterized by hemoptysis, diffuse pulmonary infiltrates, and respiratory failure. However, the treatment options for DAH remain limited, and DAH-related studies are needed to explore more effective therapeutic directions for DAH for better disease management and improved prognosis. Methods: This study utilized the pristane-induced DAH murine model to mimic the pathological process of DAH in patients with SLE. Proteomic analysis was conducted to detect differentially expressed proteins (DEPs) in the plasma of surviving and non-surviving mice, followed by an analysis of biological functions and pathways. The most significant DEP was then confirmed in the plasma of SLE patients with or without DAH, as well as in the DAH murine model with or without fatal outcomes. Finally, the therapeutic value of haptoglobin (Hp) replacement was validated in a DAH murine model through lung histopathology, RT-qPCR, and survival analysis. Results: This study identified a total of 178 DEPs, with 118 up-regulated and 60 down-regulated in the non-survival group. Within a set of notable Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, complement and coagulation cascades emerged as the most prominent pathway associated with the process of DAH. Later, the most significant DEP, haptoglobin (Hp), was confirmed to exhibit a significant decrease in the plasma of individuals with SLE-DAH and in the DAH murine model with poor outcomes by ELISA test. Finally, compared to the control group, the severity of DAH in the Hp treatment group was alleviated significantly, manifested by the decreased levels of pro-inflammatory cytokines (IL-6 and TNF-α), increased levels of anti-inflammatory cytokines (IL-10 and TGF-β), and decreased mortality. Conclusion: A reduction in plasma Hp levels was observed in SLE-DAH, and replacement therapy with Hp could alleviate pulmonary hemorrhage and reduce mortality in DAH mice. This study identified Hp as a potential biomarker for its clinical diagnosis and a direction for treatment.